Measurement of mass and width of the W boson at LEP - Dova, María Teresa (1999)
We report on measurements of the mass and total decay width of the W boson with the L3 detector at LEP. W-pair events produced in e+e- interactions between 161 GeV and 183 GeV centre-of-mass energy are selected in a data sample corresponding to a total luminosity of 76.7 pb-1 . Combining all final states in W-pair production, the mass and total decay width of the W boson are determined to be mW=80.61 ± 0.15 GeV and ΓW= 1.97 ± 0.38 GeV, respectively.